Propuesta del Diseño de una Planta de Faenamiento de cuyes, para la parroquia San Fernando, cantón Ambato, provincia de Tungurahua - Palacios Vargas, Diana Jazmina (2020)
In the San Fernando parish, a proposal was made for the Design of a guinea pig slaughter Plant, for being a representative species of indigenous culture and traditions; it has been convenient for the parish communities to be empowered by this great value chain that guinea pigs have, giving a business approach to your exploitation, allowing the development of the locality based on cooperation between community members, and the support entities of the parish. The proposal arose due to the fact that small producers have faced inconveniences due to the scarce technification, limited marketing channels and unknown of various ways to add value; causing producers to sell low quality specimens, without proper hygiene and slaughter standard. As slaughter is a practical problem, the research is applied for which diagnostic tools of the situation were used through interviews to key informants and field visits. The market research collected important data, such as, number of animals that produce, type of infrastructure, production process, slaughter process among others. From this perspective, a slaughter process has been proposed that contributes, to a great extent, to the improvement of guinea pig meat production, guaranteeing of better quality and asepsis. For the design of the slaughter plant, the AutoCAD 2021 and Sketchup Pro 2019 softwares were used. It was made reference to the specifications of the guinea pig slaughter guide issued by AGROCALIDAD, so that at the time of its implementation, the executing entity has the conditions and the necessary resources.